Access to Financial Services : A Review of the Issues and Public Policy Objectives - Claessens, Stijn (Oxford University Press on behalf of the World Bank, 2013)
This article reviews the evidence on the importance of finance for economic well-being. It provides data on the use of basic financial services by households and firms across a sample of countries, assesses the desirability of universal access, and provides an overview of the macroeconomic, legal, and regulatory obstacles to access. Despite the benefits of finance, the data show that use of financial services is far from universal in many countries, especially developing countries. Universal access to financial services has not been a public policy objective in most countries and would likely be difficult to achieve. Countries can, however, facilitate access to financial services by strengthening institutional infrastructure, liberalizing markets and facilitating greater competition, and encouraging innovative use of know-how and technology. Government interventions to directly broaden access to finance, however, are costly and fraught with risks, among others the risk of missing the targeted groups. The article concludes with recommendations for global actions aimed at improving data on access and use and suggestions on areas of further analysis to identify constraints to broadening access.